MOOCs (Massive Open Online Courses): A Potential Solution for Challenges in Indian Higher Education - Hooda, Madhuri; Bhardwaj, Karuna (Voices of Teachers and Teacher Educators, 2019)
Higher education in India is undergoing considerable changes to develop a good education system. The Indian education system faces many difficulties and challenges such as equity, quality education, access to education and individualised learning. Fifty percent of the Indian population is under the age of 25 and this requires the setting up of many universities and colleges to provide access to education for all young learners, which could result in huge expenditure. Although the numbers of educational institutions are being increased by the government, there is still a gap between the demand and supply. India is a populous and developing country that needs to not only reduce expenditure, but also provides quality education. MOOCs (Massive Open Online Courses) can be seen as a potential solution for the Indian higher education system.